RESPONS TANAMAN LIDAH BUAYA (Aloe vera MILL) TERHADAP BEBERAPA JENIS PUPUK ORGANIK - Dyan Respati Puteri; Syaripah Ulpah; Maizar Maizar (UIR Press, 2017)
The purpose of this study was to determine the response of aloe vera plants to several types of organic fertilizers. The design used in this study was a Completely Randomized Design (CRD) with 7 organic fertilizer treatments namely: Without organic fertilizer, chicken manure, cow manure, goat manure, oil palm empty bunch compost, corn bokashi, and vermicelli Each treatment consisted of 5 replications so that there were 35 units of experiment with 4 plants per plot, two of them were used as sample plants, and the whole plant became 140 plants. The parameters observed in this study were the increase in the number of leaf midribs (leaves), leaf width (cm), leaf midrib length (cm), leaf weight (gram), plant biomass (gram) and root volume (ml). The last observation data were analyzed statistically and continued with a BNJ follow-up test at the level of 5%. Research shows that the response of aloe vera plants to several types of organic fertilizers significantly affects the parameters of leaf width, leaf midrib length, leaf weight, and plant biomass. The best treatment on cow manure with a dose of 50 g / plant.